(untitled) (Gestión y Gerencia, 2018)
This paper studies the State intervention impact on the individual market of a processing company of washed sand and chopped stone, during the period 2014-2015. The research is descriptive, with field and documentary design, with data taken directly from the administrative staff of the company APN, C.A. and the monthly financial reports, as well as from the costs structure and product prices. The company’s market is described and its fundamental elements are analyzed: operating costs (fixed and variable), total demand (public and private), and prices of aggregate material (public sector and private sector) and the utility of selling a unit produced to each sector. It is observed: - That the distribution of the aggregate material is imposed by the State; - and the sales price for this is lower than the sales price for private clients, a situation that adversely affects the profits of the company because they does not cover the operating costs of production; the company must comply with such conditions because they are administrative decisions; the market qualifies as a duopoly. Average losses estimated in 25.59% per cubic meter sold.